Kolmanskop : an industrial heritage resource or only a tourist attraction? : the assessment of value with regard to Kolmanskop Ghost Town and the industrial landscape of the Sperrgebiet National Park, Namibia - Alexander, Nicola (School of Architecture, Planning and Geomatics, 2015)
Includes bibliographical references (p. 107-110).